2017
DOI: 10.1177/0016986217690228
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Gifted Education

Abstract: Early educational experiences are formative for establishing a foundation of academic success in childhood and adolescence (Reynolds, 2000; Reynolds, Temple, Robertson, & Mann, 2001). It is estimated that there are almost 8,000,000 preschool-aged children in the United States, and nearly half of those children (3,669,000) attend some type of preschool program (Maxwell, 2012). With the passing of the Every Student Succeeds Act (ESSA), the United States has validated its priority on early childhood learning. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 49 publications
0
11
0
2
Order By: Relevance
“…The EFL teachers in this study reported a host of perceived challenges. Researchers outside the context of Iran have referred to the majority of these barriers, including time (Goodnough, 2010;Oswald & de Villiers, 2013;VanTassel-Baska & Stambaugh, 2005); energy (Goodnough, 2010); class size (Oswald & de Villiers, 2013); lack of practical knowledge about differentiation (Kettler et al, 2017;Oswald & de Villiers, 2013); opposing beliefs (Kettler et al, 2017); lack of motivation, particularly financial (Kettler et al, 2017); lack of administrative support (Goodnough, 2010;VanTassel-Baska & Stambaugh, 2005); and limited resources (Goodnough, 2010). The barriers reported in this study can be grouped according to their nature or by varying degrees of preponderance in different locales.…”
Section: Discussionmentioning
confidence: 94%
“…The EFL teachers in this study reported a host of perceived challenges. Researchers outside the context of Iran have referred to the majority of these barriers, including time (Goodnough, 2010;Oswald & de Villiers, 2013;VanTassel-Baska & Stambaugh, 2005); energy (Goodnough, 2010); class size (Oswald & de Villiers, 2013); lack of practical knowledge about differentiation (Kettler et al, 2017;Oswald & de Villiers, 2013); opposing beliefs (Kettler et al, 2017); lack of motivation, particularly financial (Kettler et al, 2017); lack of administrative support (Goodnough, 2010;VanTassel-Baska & Stambaugh, 2005); and limited resources (Goodnough, 2010). The barriers reported in this study can be grouped according to their nature or by varying degrees of preponderance in different locales.…”
Section: Discussionmentioning
confidence: 94%
“…Perhaps an "advanced development" verification based on character descriptors and functional testing should be considered for gifted children who are not yet school age. This could be determined by observational data on functional developmental indicators such as the mismatch between a child's level of performance and the typical learning activities of the center (Kettler et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Gifted children may appear more advanced when compared to peers in a variety of ways (Bildiren, 2018;NAGC, 2019), such as in language development (Bildiren, 2018;NAGC, 2019) mathematical (Bildiren, 2018) or numeracy skills (Adedoyin & Chisiyanwa, 2018), inquiry and curiosity (Kettler et al, 2017), or even entrepreneurship (Shavinina, 2008). Children can be gifted globally, or they may exhibit high abilities in one or more areas that occur alongside average abilities (Kettler et al, 2017) or another exceptionality (NAGC, 2019). Gifted characteristics can also be observed in very young children.…”
Section: Literature Reviewmentioning
confidence: 99%
“…De manera similar a las creencias sobre la diversidad, en lo que refiere a la AC existe, a nivel discursivo, una intencionalidad de reconocerla y abordarla en el aula como otra necesidad educativa, lo cual contradice visiones encontradas en la literatura sobre discursos "anti-intelectuales" por parte de profesionales de la educación, quienes rechazan la idea de abordar la AC por considerarla elitista (Hafenstein et al, 2017;Kettler et al, 2017). Sin embargo, también se aprecia una visión restringida sobre la AC, la cual pone mayor énfasis en el rendimiento, sin necesariamente considerar otros elementos propios de su expresión, como por ejemplo la creatividad.…”
Section: Discussionunclassified